Sarcopenia parameters in active older adults - an eight-year longitudinal study - Kaja Teraž; Uros Marusic; Miloš Kalc; Boštjan Šimunič; Primož Pori; Bruno Grassi; Stefano Lazzer; Marco Vicenzo Narici; Mojca Gabrijelčič Blenkuš; Pietro Enrico di Prampero; Carlo Reggiani; Angelina Passaro; et al. (BMC, 2023)
Abstract Backgroud Sarcopenia is a common skeletal muscle syndrome that is common in older adults but can be mitigated by adequate and regular physical activity. The development and severity of sarcopenia is favored by several factors, the most influential of which are a sedentary lifestyle and physical inactivity. The aim of this observational longitudinal cohort study was to evaluate changes in sarcopenia parameters, based on the EWGSOP2 definition in a population of active older adults after eight years. It was hypothesized that selected active older adults would perform better on sarcopenia tests than the average population. Methods The 52 active older adults (22 men and 30 women, mean age: 68.4 ± 5.6 years at the time of their first evaluation) participated in the study at two time points eight-years apart. Three sarcopenia parameters were assessed at both time points: Muscle strength (handgrip test), skeletal muscle mass index, and physical performance (gait speed), these parameters were used to diagnose sarcop0enia according to the EWGSOP2 definition. Additional motor tests were also performed at follow-up measurements to assess participants' overall fitness. Participants self-reported physical activity and sedentary behavior using General Physical Activity Questionnaire at baseline and at follow-up measurements. Results In the first measurements we did not detect signs of sarcopenia in any individual, but after 8 years, we detected signs of sarcopenia in 7 participants. After eight years, we detected decline in ; muscle strength (-10.2%; p < .001), muscle mass index (-5.4%; p < .001), and physical performance measured with gait speed (-28.6%; p < .001). Similarly, self-reported physical activity and sedentary behavior declined, too (-25.0%; p = .030 and − 48.5%; p < .001, respectively). Conclusions Despite expected lower scores on tests of sarcopenia parameters due to age-related decline, participants performed better on motor tests than reported in similar studies. Nevertheless, the prevalence of sarcopenia was consistent with most of the published literature. Trial registration The clinical trial protocol was registered on ClinicalTrials.gov, identifier: NCT04899531.